基于可靠度的组合桥梁设计及维护策略(英文) - 张慕圣; 陈锐斌 (Jianzhu Gangjiegou Jinzhan)
Currently,the design practice of highway bridges around the world are moving towards limit states design,a reliability-based design procedure.Canadian Highway Bridge Design Code（CHBDC）is the first design code entirely developed based on limit states design philosophy,including foundations and FRP components.However,reliability of a structure decreases in service due to environmental attacks and material deterioration such as fatigue,corrosion and many other reasons.Therefore,the structure should be inspected periodically,and the reliability of the structure should be evaluated according to its age and field data.If its reliability is reduced to a certain level,a repair should be scheduled as well as some preventive maintenance measures should be implemented to prevent further deterioration.Recently,many research works have been conducted to investigate reliability-deterioration mechanisms for each type of infrastructure and its components,optimize the inspection and maintenance strategy,predict remaining service life,estimate its life cycle cost.This paper is focused on the study of reliability-deterioration mechanisms of slab on steel girder bridges due to fatigue and corrosion of steel girders as well as corrosion of reinforcement in the deck slab.Examples will also be given to illustrate the proposed life cycle management strategy for composite slab on steel girder bridges.